Analysis of Factors Related To Adolescents Preparedness in The Disaster-Prone Areas In Lempake Village, Samarinda - Dwi Rahmah Fitriani; Alfi Ari Fakhrur Rizal; Milkhatun Milkhatun; Ni Wayan Wiwin Astiningsih (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The results of this study indicated that the characteristics of the respondents were mostly in their early adolescence with 408 people (67.8%), 346 women (57.1%) and 317 people with a high school education background (53.4%). Anxiety factor having moderate anxiety were 436 people (71.9%), the coping mechanism factor of the respondents having an adaptive coping mechanism were 338 people (55.8%) and the respondents social support factor having good social support were 319 people ( 52.6%) and most of the respondents (349 people (57.6%)) had a good preparedness. The results of the bivariate analysis showed that the p value <α (α = 0.05, CI; 95%) which indicates that there is a relationship between anxiety factors, coping mechanisms and social support with adolescent preparedness. The results of multivariate analysis using Logistic Regression (OR value: 5.1) found that the anxiety factor was the most significant factor associated with adolescent preparedness